1992
DOI: 10.1115/1.2906660
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Ducted Engine Nacelle Aerodynamics and Integration Testing

Abstract: Future aircraft engine development may lead to Advanced Ducted Engines (ADE), which have a bypass ratio significantly higher than present turbofans. The increases in bypass ratio will dictate larger diameter nacelles and an increasing importance of the nacelle aerodynamics and wing integration aerodynamics. A series of isolated wind tunnel tests was therefore designed and conducted by PWA and MTU to investigate inlet, nozzle, and reverser aerodynamics. Additional installed testing was done in cooperation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In independent experimental studies, McCall et al [41] and Ingraldi et al [42] reported that interference drag penalties in high-bypass ratio nacelle installations were approximately the same as for conventional-type nacelles (BP R = 18 vs. BP R = 6 in the latter study). Instead, wave drag due to shock waves forming on the nacelle surface was identified a challenge in short nacelles [40].…”
Section: Previous Work On Low-fpr Propulsor Performancementioning
confidence: 99%
“…In independent experimental studies, McCall et al [41] and Ingraldi et al [42] reported that interference drag penalties in high-bypass ratio nacelle installations were approximately the same as for conventional-type nacelles (BP R = 18 vs. BP R = 6 in the latter study). Instead, wave drag due to shock waves forming on the nacelle surface was identified a challenge in short nacelles [40].…”
Section: Previous Work On Low-fpr Propulsor Performancementioning
confidence: 99%